Study of Phytosociological Parameters and Carbon Stock between Two Community Forest of Different Ecological Regions of Udaypur District of Nepal - Ayer, Santosh (Journal of Multidisciplinary Research Advancements, 2023)
This study compared the regeneration status, vegetation diversity, stand structure, and carbon stock of two community-managed forests located in different ecological regions of Nepal. A total of 61 concentric sample plots were investigated by using systematic random sampling with 1 % sampling intensity. The phytosociological parameters of trees and regeneration density were calculated using standard techniques. The aboveground tree carbon was estimated using a non-destructive method. Correlation analysis was performed to assess the variation of carbon stock with biomass, stand density, tree diameter at breast height (DBH), tree height, basal area, and seedling density. Janata community forest (CF) had higher regeneration than the Hazare CF, with a bell-shaped distribution of DBH in Janata CF and an interrupted curve in Hazare CF. Both forests were dominated by Shorea robusta. Hazare CF had higher Shannon diversity index, Simpson's index, and evenness index, while Janata CF had higher carbon stock. The observed differences in the studied parameters between the two community forests can be attributed to the difference in ecological factors such as temperature, rainfall, soil nutrient availability, and management practices. Future studies focusing on investigating the underlying factors driving the observed patterns and relationships, such as the effects of disturbance, climate, and management practices on forest structure and function are also needed. These findings have important implications for forest management and conservation policies, especially in the context of climate change mitigation and biodiversity conservation.